Construcción de un prototipo de robot velocista desde un estudio aerodinámico (2024)
This thesis focuses on the construction of a sprinter robot prototype from an aerodynamic study using those principles, with the aim of improving its speed and energy efficiency. The study is structured in three chapters that cover from the characterization of benchmarks from world competitions in the category of sprinter robots, through the aerodynamic design of the robotic vehicle, to the construction and evaluation of the sprinter robot prototype.